Martinez-Frias syndrome: Evidence of linkage to RFX6 mutation - Maria Carmen Mora; Joseph Volk; Areli K. Cuevas-Ocampo; Kaitlyn E. Wong; Gary Rockwell; Michael V. Tirabassi; David B. Tashjian (Elsevier, 2014)
Martinez-Frias Syndrome (MFS) is a rare disorder characterized as an autosomal recessive disease. It has been described as a disorder of duodenal atresia, extrahepatic biliary atresia, hypoplastic pancreas, intrauterine growth retardation (IUGR), and initially described with tracheoesophageal fistula. We present a case report of a preterm infant with a diagnosis of MFS, and a review of the literature. The constellation of symptoms described varies between the limited number of cases reported; this case presented is rare as the patient's course was complicated by cerebral ischemia something not previously described.